THE DEVELOPMENT OF MENTAL MODELS TEST ON HEAT AND TEMPERATURE - Rian Priyadi; Markus Diantoro; Parno Parno (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
PENGEMBANGAN INSTRUMEN MODEL MENTAL PADA TOPIK SUHU DAN KALORAbstrakKami telah mengembangkan tes sebagai analisis model mental pada materi suhu dan kalor. Penelitian pengembangan ini didasarkan pada pentingnya mengetahui tingkatan model mental siswa. Model mental merupakan representasi internal siswa dalam memahami sebuah konsep. Penelitian ini menggunakan model pengembangan 4-D. Produk yang dihasilkan merupakan instrumen analisis model mental berupa soal terbuka. Selanjutnya, instrumen tes model mental diujicobakan kepada responden (N=90) untuk mengukur validitas dan reliabilitas. Tes yang telah dikembangkan terdiri dari 8 soal dengan reliabilitas sebesar 0,667. Berdasarkan analisis data, instrumen tes model mental pada materi suhu dan kalor layak digunakan sebagai instrumen penilaian. AbstractWe have developed test inventory as an analysis of mental models on heat and temperature topics. This development research based on the importance of knowing the level of students' mental models. The mental models are a student’s internal representation of understanding a concept. This study uses a 4-D model. The product being produced is a mental model analysis consists of open-ended questions. Furthermore, mental models test were tested on respondents (N = 90) to measure the validity and reliability. The test that has been developed consists of 8 questions with a value of reliability is 0.667. Based on data analysis, the test of mental models on heat and temperature topics is feasible to use as an assessment instrument.